PROGRAM-METHODICAL PROVISION OF PHYSICAL EDUCATION IN EDUCATION INSTINUTIONS OF KHERSON PROVINCE (1864-1914) - Verbytskyi, Vitalii A. (Educological discourse, 2015)
The article is devoted to the study school programs of physical education in high schools of South of Ukraine in the second half of XIX-th – beginning of XX-th century. On example of gymnasiums Kherson province was analyzed programmatic-methodological support to the process of physical education. Concluded that in the pre-revolutionary period there was no unified educational programs of physical education. The main documents that used during the lessons were author programs which compiled by teachers of gymnastics based on various gymnastic systems.